If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8z + -29 = -23 + 3z Reorder the terms: -29 + 8z = -23 + 3z Solving -29 + 8z = -23 + 3z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-3z' to each side of the equation. -29 + 8z + -3z = -23 + 3z + -3z Combine like terms: 8z + -3z = 5z -29 + 5z = -23 + 3z + -3z Combine like terms: 3z + -3z = 0 -29 + 5z = -23 + 0 -29 + 5z = -23 Add '29' to each side of the equation. -29 + 29 + 5z = -23 + 29 Combine like terms: -29 + 29 = 0 0 + 5z = -23 + 29 5z = -23 + 29 Combine like terms: -23 + 29 = 6 5z = 6 Divide each side by '5'. z = 1.2 Simplifying z = 1.2
| x=4+0.3333333333y | | S-0.18s=0.82s | | 12x+40-10x=-16-6x | | 121x^2=36 | | 25+30x=45+20x | | 2p-4=-19+7p | | -8=20+7x | | cos(pi/2)^2 | | (1250q-8q^2)-(125+6q^2)=0 | | 6(n-3)=3 | | X-4.7=1.3 | | .1=-16t^2+4t+2 | | 3y^2+29y-10= | | 3x+10+4x-5+90=180 | | -4(u+2)=3 | | -4/3x=-16/21 | | 4x^4=16 | | 2=6(m-9) | | 7x+2y+9z=250 | | 9/10T | | 2=(6-9) | | 4(f-6)=8 | | 5x+7.5=60 | | 6(t-7)=8 | | 7x+2y+9z= | | 5/9x=-35/4 | | 9x+12=7x+20 | | 10(s-8)=165 | | 28x^-2/7y-3 | | 8.14x+1=70.7281+x | | -6(h-6)=2 | | 3/8x=9/2 |